Proceso de enseñanza y aprendizaje de Física mediado con la plataforma electrónica Arduino en el nivel de educación secundaria - Albito Carrión, Daniela Carolina (2024)
The accelerated evolution of technology has allowed educators to present new methodologies that achieve greater student involvement in the teaching-learning process, likewise developing the skills demanded by the 21st-century digital society. This research entitled: Teaching and learning process of Physics mediated with the Arduino electronic platform at the secondary education level, aims to analyze the importance of teaching and learning Physics through the Arduino electronic platform. For this purpose, a research with a cross-sectional design and a descriptive exploratory scope was methodologically proposed. The methodological approach is qualitative, focused on the description of interpretations, experiences and meanings, and the methods used are: inductive, deductive and statistical. For the collection of information, the techniques of documentary review and field study were used, as instruments the search log, bibliographic and content files, and the questionnaire.The results obtained of the documentary review determined that there was a widespread tendency towards using Project-Based Learning (PBL) as an active methodology to employ this tool. Inside of the field study, it was found that 90% of the students responded positively to the teaching of Physics using Arduino; To sum up, this technological tool helps enhance student learning, making them the principle protagonist in their education, allowing them to work on problem-solving skills and promoting collaborative work, while adapting to the demands and challenges this current society. Keywords: Physics with Arduino, thermodynamics, Project Based Learning, Teaching – learning